Fragmentation Studies And Metal Accounting Successes At Kopanang Mine. - Summary - FJ Fourie (The Southern African Institute of Mining and Metallurgy, 2007)
Lack of success in attempts to develop viable large-scale continuous mining techniques (previously reported by MP o?Hare in 2004) led the team at Kopanang to explore alternative solutions to their ongoing need for improved profitability. By calling into question the basic assumptions around the stoping of narrow tabular deposits of gold, fragmentation and more particularly, the range of sizes of blasted rocks eventually became the focus of serious study. This background is briefly covered before the sequence of the investigations is described. So far, some of the ?rules of thumb? derived over the years have been confirmed, albeit for totally different reasons than those from which they arose; some persistent theories on gold loss have been debunked, and some new ones have been developed. Blast optimisation (the means by which desired fragmentation is achieved) has been based on tailoring energy to rock characteristics in an innovative packaging design for explosive charges. Other beneficial consequences arising from the work include increased production volume and gold output, a decrease in milling consumables, and the Mine Call Factor is being maintained at a level previously thought to be unachievable. This is very much a ?work in progress?, and it is empirical in its approach. The authors are the first to recognise that they have yet to determine in absolute measures why some of the innovations have had the effect that has been observed. Also that there other factors which may contribute to the result, but which have not yet been examined. Nevertheless, publication of the work completed so far is felt to be justified; firstly on the basis of the achievements themselves, and secondly for the benefit of others in the industry for whom similar problems exist. Statistical reports of the effects on the business are included at the end of the report. Detailed laboratory test results have been separated into an appendix, leaving salient graph and tabulated data in the main text. For ease of reading, units of measurement for particle sizes below 1mm are described in microns, but millimetres have been retained for those at that size or greater.